PERAN META DATA MANAGEMENT DALAM PERSONALISASI LAYANAN E-COMMERCE: STUDI KASUS PADA BUKALAPAK - Nurbaiti Nurbaiti; Nur Hamidah Harahap; Raulanda Dwi Putra; Salma Agita Sitepu (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The rapid growth of the e-commerce industry in Indonesia demands innovations in service personalization to enhance customer experience and loyalty. This study examines the role of metadata management in supporting service personalization on the Bukalapak platform. Using a qualitative descriptive approach through literature review and online surveys, this research highlights how effectively managed metadata can improve the relevance of product recommendations and user interactions. The findings indicate that good metadata management significantly contributes to user satisfaction and loyalty, despite challenges related to data volume, security, and privacy. This study provides valuable insights for developing user-oriented e-commerce services in Indonesia.